2015
DOI: 10.1007/s10640-015-9894-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Sustainability: Assessing Fishery Management Strategies

Abstract: We develop a theoretical framework to assess the sustainability of fishery management strategies, when the bioeconomic dynamics are marked by uncertainty and several conflicting objectives have to be accounted for. Stochastic viability ranks management strategies according to their probability to sustain economic and ecological outcomes over time. The approach is extended to build stochastic sustainable production possibility frontiers representing the trade-offs between sustainability objectives at any risk l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Setting bounds on the latter could be considered a sort of "ecological" constraint, similar in spirit to the ones considered in the stochastic viability literature (e.g. [11,19,20]). Such an operation would increase the problem's dimensionality considerably, but it can be addressed, so long as the total number of distributions across indicators is not excessive.…”
Section: Q2: If Carbon Budget B Is Chosen What Proportion Of Distribmentioning
confidence: 99%
See 2 more Smart Citations
“…Setting bounds on the latter could be considered a sort of "ecological" constraint, similar in spirit to the ones considered in the stochastic viability literature (e.g. [11,19,20]). Such an operation would increase the problem's dimensionality considerably, but it can be addressed, so long as the total number of distributions across indicators is not excessive.…”
Section: Q2: If Carbon Budget B Is Chosen What Proportion Of Distribmentioning
confidence: 99%
“…Martinet [19] and Doyen and Martinet [12] made an explicit connection between stochastic-viability models and sustainability concepts such as the maximin criterion. Doyen et al [13] and Martinet et al [20] applied similar ideas to a setting of sustainable fishery management. In the stochastic component of this work, emphasis was placed on calculating the probability of different policies respecting the various sustainability constraints.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it has been found that oceanic climate changes caused by human activities are threatening fishery resources (McKelvey and Golubtsov, 2015;Martinet et al, 2015). Likewise, it is considered that some fish farming activities tend to cause ecological risks.…”
Section: Introductionmentioning
confidence: 99%
“…As oceanic climate changes are poorly predictable, the harvest of some coastal fishing countries is also affected by a deteriorating oceanic climate. For instance, Jackmackerel fishery in Chile encountered uncertainty, as threatened by El Niño (McKelvey and Golubtsov, 2015;Martinet et al, 2015). With respect to the impact of climate change, an essential point is a sea-level rise.…”
Section: Introductionmentioning
confidence: 99%